Effects of macroeconomic variables on stock prices in Malaysia: an approach of error correction model - Mohd Thas Thaker, Mohamed Asmy; Rohilina, Wisam; Hassama, Aris; Amin, Md. Fouad Bin (Serials Publication, 2010)
This paper attempts to examine the short-run and long-run causal relationship between Kuala Lumpur Composite Index (KLCI) and selected macroeconomic variables namely inflation, money supply and nominal effective exchange rate during the pre and post crisis period from 1987 until 1995 and from 1999 until 2007 by using monthly data. The methodology used in this study is time series econometric techniques i.e. the unit root test, cointegration test, error correction model (ECM), variance decomposition and impulse response function. The findings show that there is cointegration between stock prices and macroeconomic variables. The results suggest that inflation, money supply and exchange rate seem to significantly affect the KLCI. These variables considered to be emphasized as the policy instruments by the government in order to stabilize stock prices.